Identification Of Potential Genotypes Of Coriander (Coriandrum Sativum L.) Suitable For Rainfed Vertisols (Applied Biological Research, 2014)
The present study was conducted during 3 consecutive years (2009-2010 to 2011-12) at Horticultural Research Station, Lam, Andhra Pradesh (India)  to evaluate ten promising and diverse genotypes of coriander (Coriandrum  sativum L.) procured from different states of India. Maximum yield was  achieved in genotype LCC-237 (959.0 kg ha-1) followed by LCC-236 (897  kg ha-1) which were on par with each other but significantly superior over check variety Sudha (723 kg ha-1). Considering the stability parameters for  yield, genotypes RKD-13 and LCC-236 with almost unit regression (-0.90  and 1.12, respectively) may be considered as stable genotypes. The genotype  LCC-236 with significant deviation in regression coefficient may be  considered as plastic genotype that outperformed other genotypes  including best check (Sudha) in all the seasons tested. The mean  performance of genotype RKD-13 was significantly lower than check  Sudha, hence considered as a poor yielder. Early flowering and maturity,  coupled with superiority in these traits, when correlated with yield was  found to be the reason for better performance of genotype LCC-236 under diverse environmental conditions. This genotype also possessed high  essential oil content than other genotypes evaluated.
Keywords: Coriander; rainfed vertisols; soil moisture; stability; yield